2022
DOI: 10.1017/jog.2022.85
|View full text |Cite
|
Sign up to set email alerts
|

Large-ensemble climate simulations to assess changes in snow stability over northern Japan

Abstract: To examine the influence of global warming including increased heavy snowfall frequency on the potential of natural dry snow avalanche frequency and magnitude, we estimated the frequency of weak layer formation and the associated slab overload above the weak layer over northern Japan. The estimation was numerically performed using climate models' output for 1800 winter simulations in each of the historical (1951–2010) and +4°C experiments by forcing a physical-based snowpack model with the result of the climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Enhanced temperatures hinder the formation of weak layers by directly affecting the temperature gradient across the snowpack (Richter et al, 2020). Interestingly, Katsuyama et al (2022) also found a decline in the proportion of persistent weak layers based on climate projections for Northern Japan.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Enhanced temperatures hinder the formation of weak layers by directly affecting the temperature gradient across the snowpack (Richter et al, 2020). Interestingly, Katsuyama et al (2022) also found a decline in the proportion of persistent weak layers based on climate projections for Northern Japan.…”
Section: Discussionmentioning
confidence: 87%
“…Unlike previous studies relying on bulk snow cover properties or simple snow instability metrics (Lazar and Williams, 2008;Castebrunet et al, 2014;Katsuyama et al, 2022), we used machine learning models to classify dry-and wet-snow AvDs from simulated snow stratigraphy and meteorological variables. This enabled us to comprehensively evaluate the impact of different climate scenarios on snow avalanche activity, investigate changes in seasonality, and highlight causes of projected changes beyond a mere decrease in snow depth or shortening of the snow season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation